2012
DOI: 10.7314/apjcp.2012.13.12.6197
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of EZH2 by RNA Interference Inhibits Proliferation and Invasion of ACHN Cells via the Wnt/β-catenin Pathway

Abstract: Although enhancer of zeste homolog 2 (EZH2) has been reported as an independent prognostic factor in renal cell carcinoma (RCC), little is known about the exact mechanism of EZH2 in promoting the genesis of RCC. However, several studies have shown that dysregulation of the Wnt/β-catenin signaling pathway plays a crucial role. Therefore, we determined whether EZH2 could affect ACHN human RCC cell proliferation and invasion via the Wnt/β-catenin pathway. In the present study, we investigated the effects of short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…EZH2 is the histone H3 lysine 27 methyltransferase of polycomb-repressive complex 2 and is overexpressed in multiple cancer types (62). Several EZH2-related proteins were detected by western blot analysis in both A549 and non-small cell lung cancer (NSCLC) H1299 cell lines and decreased expression of both β-catenin and bcl-2 was found in consensus with the previous finding that EZH2 can ultimately enhance Bcl-2 expression via the activation of wnt/β-catenin signaling (63). Thus, Huaier may induce apoptosis in lung cancer cells via the miR-26b-5p-EZH2-mediated wnt/β-catenin pathway (Fig.…”
Section: Apoptosis Induction By Huaiersupporting
confidence: 73%
“…EZH2 is the histone H3 lysine 27 methyltransferase of polycomb-repressive complex 2 and is overexpressed in multiple cancer types (62). Several EZH2-related proteins were detected by western blot analysis in both A549 and non-small cell lung cancer (NSCLC) H1299 cell lines and decreased expression of both β-catenin and bcl-2 was found in consensus with the previous finding that EZH2 can ultimately enhance Bcl-2 expression via the activation of wnt/β-catenin signaling (63). Thus, Huaier may induce apoptosis in lung cancer cells via the miR-26b-5p-EZH2-mediated wnt/β-catenin pathway (Fig.…”
Section: Apoptosis Induction By Huaiersupporting
confidence: 73%
“…Here, we confirmed that the Wnt/β-catenin pathway was stimulated by EZH2 in HeLa and SiHa cells, with activation of target genes, resulting in the promotion of cell growth and tumor formation (Figure 4). Additionally, EZH2-stimulated epigenetic silencing contributes to constitutive activation of Wnt/β-catenin signaling and consequential cellular proliferation in hepatocellular carcinoma [55], gastric cancer [28], renal cell carcinoma [56], colon cancer [57] and breast cancer [58]. In the mechanism of the EZH2-mediated activation of Wnt/β-catenin signaling to promote carcinogenesis, EZH2, which acts as a transcriptional repressor, represses Wnt antagonists, including RAF1, CXXC4, AXIN2/betaTrCP and p53 [13, 28, 55, 59], by decreasing the acetylation of H3K27, thereby promoting the development of different types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, GSK-3β expression was found to be markedly increased after transfection of EZH2 siRNA to promote the proliferation and invasion of ACHN cells via activation of the Wnt/β-catenin signaling pathway [56]. TP53 was first verified as a target gene of EZH2 in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, the Wnt/β-catenin signaling pathway serves a crucial role in cell proliferation and tumor cell invasion (40)(41)(42). The effect on the expression of the Wnt/β-catenin signaling pathway was investigated in the present study by western blotting in order to elucidate the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%